Sistem Pendukung Keputusan Untuk Penentuan Rumah Tidak Layak Huni Di Desa Lubuk Besar Kecamatan Datuk Lima Puluh Dengan Menggunakan Metode MOORA - Aygisella, Licha (CV. Graha Mitra Edukasi, 2024)
Pneumonia Assistance for uninhabitable houses (RTLH) is a problem that is of serious concern to the government of Lubuk Besar Village. At the Lubuk Besar Village Office, which still uses a manual method in determining recipients of uninhabitable housing assistance, data processing has not been computerized. This assistance is obtained if the prospective beneficiary is deemed to meet the requirements and criteria that have been determined, for example: the floor is still dirt, the walls are still bamboo, the roof structure is still thatch, the land area and so on. However, the existence of problems in determining the assistance made it difficult for the selection of prospective recipients of house renovation assistance. One solution to this problem is to use a Decision Support System (SPK) that can assist the Lubuk Besar Village Office in making decisions about determining recipients of uninhabitable housing assistance (RTLH) so that they are right on target. The MOORA method is a method that optimizes many objectives based on ratio analysis. the way this method works is to determine the ranking quickly and on target and to find out the highest to lowest scores in a selection for determining uninhabitable houses in Lubuk Besar Village, Datuk Lima Puluh District